2020
DOI: 10.1186/s12935-020-01666-1
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0015756 promotes the progression of ovarian cancer by regulating miR-942-5p/CUL4B pathway

Abstract: Background Ovarian cancer (OC) is the gynecologic cancer with the highest mortality. Circular RNAs (circRNAs) play a vital role in the development and progression of cancer. This study aimed to explore the potential role of circ_0015756 in OC and its molecular mechanism. Methods The levels of circ_0015756, microRNA-942-5p (miR-942-5p) and Cullin 4B (CUL4B) were determined by quantitative real-time PCR (qRT-PCR) or Western blot assay. Cell proliferation, apoptosis, migration and invasion were assessed by Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Their function occurs through sponge of corresponding miRNAs. Circ-0015756 increases the progress of OC by sponging miR-942-5p and influencing the miR-942-5p/CUL4B axis [88]. Similarly, the circ-0002711/miR-1244/ ROCK1 and has-circ-0015326/miR-127-3p/MYB pathways are key players in OC with potential as therapeutic targets [89,90].…”
Section: Roles In Clinical Implications Of Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…Their function occurs through sponge of corresponding miRNAs. Circ-0015756 increases the progress of OC by sponging miR-942-5p and influencing the miR-942-5p/CUL4B axis [88]. Similarly, the circ-0002711/miR-1244/ ROCK1 and has-circ-0015326/miR-127-3p/MYB pathways are key players in OC with potential as therapeutic targets [89,90].…”
Section: Roles In Clinical Implications Of Ocmentioning
confidence: 99%
“…Numerous studies have shown that circ-0015756, circ-0002711, hsa-circ-0015326, circ-0001068, circ-0025033 and circ-KIF4A are oncogenic circRNAs with diagnostic and prognostic value in OC [88][89][90][91][92][93][94]. Their function occurs through sponge of corresponding miRNAs.…”
Section: Roles In Clinical Implications Of Ocmentioning
confidence: 99%
“…miR-942-5p has been found to have diverse biological functions in several diseases. For instance, miR-942-5p has been reported as an anti-oncogene in ovarian cancer 6 and oral squamous cell carcinoma. [10][11][12][13] In addition, Wang et al revealed that miR-942-5p was involved in the regulatory roles of lncRNA SOX2-OT on doxorubicin-induced cardiomyocyte apoptosis.…”
Section: Trim37 Overexpression Attenuates the Protective Role Of 942-5p In Lps-treated A549 Cellsmentioning
confidence: 99%
“…3,4 When ALI occurs, the injury to alveolar epithelial cells caused by lipopolysaccharide (LPS) may lead to endothelial barrier dysfunction. [5][6][7][8] Therefore, it is of potential clinical importance to protect the damaged alveolar epithelial cells from sepsis-induced ALI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation